Diverse Effects of Fluoro-Phenyl-Styrene-Sulfonamide (FPSS) on Transcription Factor Sigma B Regulons in Gram-Positive Bacillales - Sirirak Supa-amornkul; Ramita Chalearmchutidath; Nichaporn Nattawut; Phimkanya Liu; Soraya Chaturongakul (Cellular Microbiology)
Bacillales is an order of Gram-positive bacteria comprising well-known genera such as Staphylococcus, Listeria, and Bacillus. Staphylococcus aureus has been shown to cause various types of tissue and systemic infections in humans and livestock. Some isolates can be highly resistant to antibiotics hence the need to identify better drugs and drug targets. Previous studies have shown that (E)-N-(4-fluorophenyl)-2-phenylethene sulfonamide (FPSS) could inhibit activities of a bacteria-specific transcription factor sigma B. Sigma B regulons in Bacillus subtilis and in Listeria monocytogenes, including virulence factor genes in L. monocytogenes, were decreased. Since sigma B is also presented in S. aureus, we initially postulated the use of FPSS to target S. aureus sigma B activity and to attenuate its virulence gene expression. Surprisingly, qRT-PCR results revealed that FPSS induced the expression of sigma B-dependent gene asp23. RNAseq results showed 39 S. aureus genes were affected by FPSS (37 genes were upregulated and two genes were downregulated). FPSS had no effect on expression of sigB operon in S. aureus. Therefore, we hypothesized that the effects of FPSS on sigma B regulons in L. monocytogenes, B. subtilis, and S. aureus were different. FPSS may target the expression of upstream regulators of sigma B (Rsbs), particularly the stressosome proteins which are lacking in S. aureus. Indeed, in L. monocytogenes, FPSS significantly increased the rsbR expression and could, thereby, dampen the sigma B activity and downregulate the expression of sigma B-dependent virulence genes in L. monocytogenes. This study proposes a narrower spectrum of FPSS application to listerial infections, and not staphylococcal infections.